Influência do sexo e estado inflamatório sistêmico nas alterações cognitivas de pacientes portadores de esquizofrenia tratados com antipsicóticos - Oliveira, Alissandra Lima Barbosa de (2023)
Introduction: Considering the complexity of schizophrenia and that this mental disorder, in addition to affecting millions of people around the world, also affects the subject with various damages, such as hallucinations, delusions, abnormal behavior, and cognitive impairment, which influences the daily lives of these individuals who perform poorly when compared to the general population. This research investigated the relationship between cognitive performance, neutrophil-lymphocyte ratio (NLR) (a marker of systemic inflammation), and antipsychotic dosage in a chlorpromazine equivalence in men and women with schizophrenia. Methodology: A cross-sectional analysis of a previous clinical trial in patients with schizophrenia was performed. The results of complete blood counts and data from neuropsychological assessments were explored. For group comparisons, analyzes were performed using the Welch t-test and Pearson's test for correlations. Results: A higher ratio of NLR was found in females compared with males. It was possible to verify that in women, NLR is positively correlated with antipsychotic dosage and inversely with working memory. Conclusion: The data found showed that the NLR hás greater value in women using antipsychotics to stabilize the symptoms of schizophrenia than in men. Also, it was found that higher levels of NLR found in women using antipsychotic therapy influence impairments in cognitive functions when compared to males. It is envisaged that these findings may contribute to the consolidation of the neuroinflammatory and estrogenic hypotheses in schizophrenia providing evidence that women of childbearing age require lower doses of antipsychotics.